Earthquake Recurrence Estimates for Northern Caribbean Faults from Combinatorial Optimization - Uri S. ten Brink; Eric L. Geist (The Seismic Record, 2025)
We use combinatorial optimization to find the optimal spatial distribution of random samples of earthquakes (≥6.5) that minimize the misfit in target slip rates for all faults in the northeast Caribbean, and we derive magnitude–frequency relationships with uncertainties for these faults. Slip rates for many faults are derived from geodetic block models, not direct measurements, because of their underwater locations. Predicted recurrence rates for earthquakes on the East Hispaniola and Puerto Rico trench faults are 220–450 yr for moment magnitude (M) 7 and 3000–5000 yr for M 8, with the maximum feasible magnitude of M 8.2. The most frequent earthquakes with magnitudes ≥7.0 are predicted on the large upper plate strike-slip faults, Enriquillo (EF), and Septentrional faults, commensurate with the historical record. Calais et al. (2023) suggested that shortening in western Hispaniola is accommodated on the offshore Jérémie and onshore Malpasse faults north and south of EF, instead of on terrestrial faults in the western Hispaniola and EF. Because of our system-modeling approach, such a configuration predicts less frequent earthquakes on EF and western Hispaniola and Muertos convergent zones. Recurrence times of a few hundred years for M 6.7 earthquakes are predicted on the submerged faults in Mona Passage, and infrequent M > 7 earthquakes are predicted on the Virgin Islands faults.